2000
DOI: 10.1109/49.840190
|View full text |Cite
|
Sign up to set email alerts
|

Field trial results for high-speed wireless indoor data communications

Abstract: Abstract-This paper reports on the development of a flexible 5-MBd equalized M-QAM testbed for high-speed wireless data communications. The unit operates in real time and was field tested in typical indoor environments. A total of 3600 independent experiments were conducted using the testbed where one of 4-, 16-, 64-QAM constellations were transmitted, and the performance as a function of adaptive equalization and antenna selection diversity was studied. The experimental results presented here help put previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…We observed that the measured BER versus SNR is within 0.5 dB of the theoretical results. This deviation is almost certainly due to the non-Gaussian characteristics of the noise introduced by the quantization, the adaptive algorithms, the recovery loops, and the feedback of errors in the DFE, as illustrated in [19] by using simulations of the prototype system.…”
Section: Testbed Calibrationmentioning
confidence: 98%
See 3 more Smart Citations
“…We observed that the measured BER versus SNR is within 0.5 dB of the theoretical results. This deviation is almost certainly due to the non-Gaussian characteristics of the noise introduced by the quantization, the adaptive algorithms, the recovery loops, and the feedback of errors in the DFE, as illustrated in [19] by using simulations of the prototype system.…”
Section: Testbed Calibrationmentioning
confidence: 98%
“…Measurements for the RF units, such as third-order intercept point, introduced intersymbol interference (ISI), and RF power spectrum, were reported in [19]. The RF receiver noise figure was 18 dB at the receiver amplification level selected for the measurements.…”
Section: Testbed Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively equalization could be used to both increase the data rate as well as remove any ISI [1,[5][6][7][8]. In particular, the decision feedback (DF) equalizer is often selected due to its reasonable performance and ease of hardware implementation [9]. Even though ANNs offer superior performance [10], they have largely been ignored for VLC systems, which is likely due to the difficulties in hardware implementation.…”
Section: Introductionmentioning
confidence: 99%